Between nation and empire: revisiting the Russian past twenty years later - Dialla, Ada A. (Historein, 2013)
This article is a succinct presentation of the historiographical overturns in the study of Russian history that have taken place in the last twenty years following the dissolution of the Soviet Union. The main emphasis is on the ʽimperial turnʼ which undermines older historical givens but also disputes the importance of the nation/nation-state as a basic category for understanding the past.